2023
DOI: 10.3389/fsoc.2023.1158770
|View full text |Cite
|
Sign up to set email alerts
|

Tribal women empowerment through entrepreneurship: evidence from Mayurbhanj District, Odisha

Abstract: IntroductionEmpowering women in a tribal context through entrepreneurship is an approach for enabling and making them economically and socially viable. This paper aims to highlight entrepreneurship in a specific tribal context and provide insight on some instances or cases relating to women's empowerment. Although there are many initiatives from international organizations and governmental institutions to support women entrepreneurs, especially tribal women, they suffer from isolation as a result of their lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Gender equality in the workplace is not just a moral issue; it is also a strategic necessity. Research regularly shows that economically empowered women lead to more considerable societal benefits, such as increased economic growth and social cohesion ( Costa et al, 2023 ; Naveen et al, 2023 ). Comprehensive strategies and targeted activities are required to break down these barriers.…”
Section: Discussion – Complex Path To Sdg 8: Unraveling Challenges An...mentioning
confidence: 99%
“…Gender equality in the workplace is not just a moral issue; it is also a strategic necessity. Research regularly shows that economically empowered women lead to more considerable societal benefits, such as increased economic growth and social cohesion ( Costa et al, 2023 ; Naveen et al, 2023 ). Comprehensive strategies and targeted activities are required to break down these barriers.…”
Section: Discussion – Complex Path To Sdg 8: Unraveling Challenges An...mentioning
confidence: 99%
“…In a study conducted by Amulya Kumar Behera, it was discussed that the Indian government's program in educating the tribal people of the Mayurbhanj District has been running (Naveen et al, 2023). However, it was found that there still needed to be more government monitoring or supervision of education programs and a lack of coordination between relevant agencies, namely the education offices and social services, in dealing with these problems.…”
Section: Government Policymentioning
confidence: 99%
“…In the article, Amulya Kumar Behera in (Naveen et al, 2023) know parents' behavior toward their children's education. According to this article, it was found that due to economic factors, parents prefer to involve their children in profitable work.…”
Section: Low Parental Supportmentioning
confidence: 99%